2023
DOI: 10.3390/insects14030214
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Costs and Incomplete Resistance Associated with Delayed Evolution of Practical Resistance to Bt Crops

Abstract: Insect pests are increasingly evolving practical resistance to insecticidal transgenic crops that produce Bacillus thuringiensis (Bt) proteins. Here, we analyzed data from the literature to evaluate the association between practical resistance to Bt crops and two pest traits: fitness costs and incomplete resistance. Fitness costs are negative effects of resistance alleles on fitness in the absence of Bt toxins. Incomplete resistance entails a lower fitness of resistant individuals on a Bt crop relative to a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 111 publications
1
6
1
Order By: Relevance
“…In contrast to the increased female pupal weight observed in Benzon, sublethal exposure to Cry1Ac in 456LS4D resulted in significantly lower pupal weight in both females (p = 0.0002) and males (p = 0.0002), when compared to larvae fed the control diet. These observations suggest incomplete resistance [56] and mirror reports of reduced pupal weight after sublethal exposure to Cry proteins in the literature, including S. exigua exposure to Cry1Ac [33,[49][50][51]. The discrepancy in effects between Benzon and 456LS4D strains probably relates to different pleiotropic effects exerted by the concentration of Cry1Ac toxin used in this study, which represents a generally lethal and sublethal treatment for Benzon and 456LS4D, respectively.…”
Section: Effects Of Sublethal Treatment On Pupal Weightsupporting
confidence: 81%
“…In contrast to the increased female pupal weight observed in Benzon, sublethal exposure to Cry1Ac in 456LS4D resulted in significantly lower pupal weight in both females (p = 0.0002) and males (p = 0.0002), when compared to larvae fed the control diet. These observations suggest incomplete resistance [56] and mirror reports of reduced pupal weight after sublethal exposure to Cry proteins in the literature, including S. exigua exposure to Cry1Ac [33,[49][50][51]. The discrepancy in effects between Benzon and 456LS4D strains probably relates to different pleiotropic effects exerted by the concentration of Cry1Ac toxin used in this study, which represents a generally lethal and sublethal treatment for Benzon and 456LS4D, respectively.…”
Section: Effects Of Sublethal Treatment On Pupal Weightsupporting
confidence: 81%
“…Evaluation of fitness and stability in selected populations has a high level of practical importance for determining resistance risk associated with the use of insecticides and can be useful for formulating insecticide resistance management strategies (Carrière and Tabashnik 2001, 2023). Recent studies of indoxacarb resistant noctuid populations showed significantly slower growth and development, and lower fecundity in S. frugiperda (Hafeez et al 2022b) and H. armigera (Cui et al 2018) suggesting the presence of indoxacarb resistance genes in these populations was deleterious.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the main concern about the potential risks of recombinant Bt strains and GM-Bt crops is the impact on non-target beneficial species [70], the effects of introducing genes to the relevant microorganisms and unpredicted effects among others, especially food safety (Figure 4). To avoid the problem of their impact on non-target beneficial species, the main aim is to increase host specificity and persistence to achieve better efficacy and lower insect resistance [74][75][76][77]. Laboratory and field studies have been conducted on the effects of GM crops on the environment and human health, resulting in little risk for human health [76][77][78].…”
Section: Safety Of Bt Based Genetically Modified Organisms (Gmo)mentioning
confidence: 99%
“…To avoid the problem of their impact on non-target beneficial species, the main aim is to increase host specificity and persistence to achieve better efficacy and lower insect resistance [74][75][76][77]. Laboratory and field studies have been conducted on the effects of GM crops on the environment and human health, resulting in little risk for human health [76][77][78]. Risks are assessed by performing laboratory tests, followed by small-and large-scale field trials to ascertain environmental safety before the release a commercial transgenic crop.…”
Section: Safety Of Bt Based Genetically Modified Organisms (Gmo)mentioning
confidence: 99%
See 1 more Smart Citation